Developing Coastal Tourism Attractions in Padangbai Village, Karangasem, Bali - Putra, I Komang Y. S. Nesa (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
The variety of potential beach tourism attractions in Padangbai village requires the stakeholders to determine the beach attraction which needed as the priority that can be done in advance and that can be done effectively and efficiently. The objectives of this research first was to know the existing condition of a beach tourist attraction in Padangbai village which is a Bias Tugel Beach and Blue Lagoon Beach. To be able to determine the development priority of a beach tourism attraction which can be seen from 6A components of tourism development, includes attraction, accessibility, amenities, ancillary, activities, and available packages. Researchers used data collection techniques in the form of observations and interviews with informants. The informant determination technique uses using purposive sampling technique with 10 informants which consist of academics, business, community, government, and media, as the stakeholders in accordance pentahelix concept. The data analysis technique used in this research was qualitative descriptive which was analyzed by AHP (Analytic Hierarchy Process) method. The result of this research indicates that Bias Tugel Beach is a priority to develop. The determination of Bias Tugel Beach as a priority tourist attraction has an average value of each criterion from the highest to the lowest value, such as a tourist attraction of 26.5%, tourist activity criteria of 22.9%, additional service criteria of 18.5%, accessibility criteria by 14.7%, the criteria for amenities by 9.9% and the criteria for the availability of tour packages by 7.6%. Nevertheless, there are accessibilities and amenities criteria that need to be improved by the management based on tourism development 6A components..